2018
DOI: 10.3390/ijerph15051007
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Levels in Women and Children from Interior Villages in Suriname, South America

Abstract: Natural sources of mercury, historical gold mining, and contemporary artisanal and small-scale gold mining (ASGM) activities have led to mercury contamination in Suriname. Our primary objective was to evaluate mercury levels in hair of women and children from interior villages in Suriname where mercury levels in fish are elevated. We also estimated blood levels of mercury using an established mathematical conversion to facilitate comparison with other biomonitoring programs in the United States. Estimated leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Sample sizes were selected based on power analyses designed to detect differences among mercury exposures on a regional scale as indicated previously. Total mercury concentrations were determined using cold vapor atomic absorption spectroscopy (CVAAS) as reported previously [ 8 , 46 , 49 ].…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample sizes were selected based on power analyses designed to detect differences among mercury exposures on a regional scale as indicated previously. Total mercury concentrations were determined using cold vapor atomic absorption spectroscopy (CVAAS) as reported previously [ 8 , 46 , 49 ].…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
“…This study builds on an initial biomarker project examining concentrations of total mercury in hair samples from a cohort of women and children in a number of interior villages in Suriname [ 6 , 8 , 46 ]. Results from that work indicate that residents in many of the interior villages near ASGM operations or downwind from such activities are indeed exposed to high levels of mercury [ 6 , 8 , 46 ]. As reported herein, continued biomonitoring of pregnant women in Suriname supports these previous findings, with high concentrations of total mercury observed in hair of women from interior sites.…”
Section: Introductionmentioning
confidence: 99%
“…Female active involvement in ASGM activities is likely to increase exposure of Hg to children living in these communities. 29,30 Women in Africa work with their children in mining sites, thus exposing their children to Hg. 31 This study demonstrates considerable occupational exposure to Hg through self-reported use (73.3%) and biologic monitoring parameters.…”
Section: Similar To Findings In Studies Table 4 -Crude and Adjusted Amentioning
confidence: 99%
“…Pregnant women potentially exposed to complex environmental chemical and non-chemical stressors were recruited from three regions of Suriname: (1) Paramaribo, where pesticides are primarily used for residential purposes; (2) Nickerie, the major rice producing region in western Suriname where pesticide use is abundant and (3) the tropical rainforest interior, where Hg is used in artisanal gold mining and the population is highly dependent on consumption of contaminated fish. 18 Taking into account, a potential 20% lost to follow-up, we requested and were approved to consent 1200 pregnant women and their singleton birth children by the Institutional Review Boards of both the Government of Suriname and Tulane University.…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…Most of these women are primarily exposed to methylmercury from consuming contaminated fish from local artisanal gold-mining activities. 18 24 Other possible sources of exposure may include active participation in or living very close to gold mining areas. Hg concentrations from the Nickerie and Paramaribo subcohorts were similar to other studies.…”
Section: Findings To Datementioning
confidence: 99%